Evaluation the efficiency of paper and clay filters loaded with nano-silver in removing water pollutants - Ali, Sabah (University of Thi-Qar Journal of Science, 2025)
To obtain pure water free from pollutants that are harmful to humans, Nano silver was placed on circular paper filters and clay filters to filter polluted water through these filters. Clay filters are manufactured by drying the clay filter at a temperature of 200 0C and then burning it at a temperature of 1000 0C. Also, another clay filter was taken and burned at a temperature of 1000 0C. This filter was broken breaks after filtration due to the sudden rise in temperature. If the drying and thermal gradation of the clay filter is completed, the filter becomes better and stronger than the plasticized filter. Also, a circular membrane paper was taken and a layer was removed from it, and we also took filter paper, all in a circular shape. Filtration is done by a filtration device. We noticed that the removal rate of paper filters ranges between (45% to 87%) due to the speed of emptying the polluted water and allowing some pollutants to pass through them. As for clay filters, the removal efficiency are not less than 95% and the water passage is slow and did not allow pollutants to pass through them.